Writing public policy - "Smith, Catherine F." (New York, 2005)
Writing Public Policy is a practical, concise guide to writing and communicating in the public policy processes. Intended to help students understand and perform common types of communication used in solving public problems, this text explains the standards and functions of communicating in the public sector and teaches the use of selected public policy communication genres. A useful tool for any student preparing for a career in politics, government, public relations, law, public policy, journalism, social work, public health, or in any role concerned with public affairs, this text teaches skills and techniques needed to effectively communicate in the democratic process of making public policy. Presenting a general method for planning, producing, and assessing communications in a variety of real-life contexts and situations, this text includes: scenarios to illustrate the complexity in policy processes, including their diversity of contexts, the variety of actors involved, and the range of communication types produced; sample documents illustrating examples of public policy communication within different realms including state legislatures, non-profit organizations, government committees, special interest groups, and professional associations; commentary relating the scenarios and examples to the general method; and specific instructions for producing particular written or spoken communication types that are utilized in public policy processes.
Keywords: Communication in public administration